Greenhouse Gas Emissions Effect on Investor Economic Decisions: Unravelling the Nexus between Corporate Sustainability Performance and Investor Share Ownership Appetite - Siwela, Witness; Mchavi, Nyiko D.; Modisane, Cameron (International Journal of Energy Economics and Policy, 2026)
The greenhouse gas emissions dilemma faced by the Republic of South Africa is undoubtedly significant as evidenced by heavy dependence on coal-fired power plants utilised for generating electricity. Statistical data depicts the country as the ‘culprit’, positioned as the largest greenhouse gas emitter in Africa despite the backdrop of a clarion call to transition towards renewable energy. Notwithstanding that this dilemma is primarily driven by Eskom, numerous companies also contribute a fair share to this phenomenon as they attempt to balance achieving climate change mitigation targets with optimising economic value creation for investors. Inquiring the responsiveness of investors, the study aimed at determining if greenhouse gas emissions attract investor share ownership. The study employed a quantitative research design from a positivist stance to meet this objective. Accordingly, archival data were gathered from FTSE/JSE Responsible Investment Index using judgemental sampling technique. Thus, a short panel data set comprising 19 cross sections yielding 114 observations for six years were utilised for statistical panel data analysis. Adopting first differenced econometric models in data analyses, Panel Vector Autoregression Model (PVAR) for Random Effects Generalized Least Squares (GLS) regression and Random Effects Maximum Likelihood Estimator (MLE) were employed to generate the reported results. The findings indicated that investor share ownership is positively influenced by greenhouse gas emissions. As a result, the findings make notable contribution by providing new insights to investment practices in South Africa within the purview of pursuing climate change mitigation targets.